Penerapan Kontrol Berbasis Suara Pada Game Pesawat Tempur Menggunakan IBM Watson - Zulfikar Fahmi Falakh; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Simulation games are a type of game where the player controls one or more virtual lives. One of the subgenres of the simulation game is a combat aircraft simulation which simulates its movements. One of the tools used to develop aircraft simulation games is the air strike starterkit which is found at the unity asset store. But in the air strike starterkit there are no features for the natural user interface. This makes playing experience less attractive than if there is a natural user interface feature. Therefore in this study the researcher will apply one of the starterkit air strike user interface interfaces using the IBM Watson library. In testing researchers used validity testing, FPS, play experience, command accuracy and delay. The results of validity testing are 100% valid. In the FPS test produces an FPS of 83. As well as in the testing experience of playing produces an increase in all aspects of the component game experience question in-game. In testing the accuracy results in a accuracy rate of 60%. The delay test produces the longest delay of 12 seconds at a connection speed of 10 kb / s and the fastest delay of 2 seconds at an internet speed of 1000 kb / s